Performance evaluation of an alternative artificial wetlands system used as wastewater treatment - Pérez Salazar, Roy; Alfaro Chinchilla, Carolina; Sasa Marín, Jihad; Agüero Pérez, Juan (Uniciencia, 2013)
In Costa Rica wastewaters are usually deposited in septic tanks where settling processes occur with effluent infiltration into the ground subsurface. This practice presents a major risk to human health and a negative impact on the environment due to possible groundwater contamination. The following case study presents the application of an artificial subsurface horizontal wetland as a low-cost alternative using a rooted emergent macrophyte system for the treatment of sewage wastewater generated within a cosmetic and pharmaceutical manufacturer. The Cyperus papyrus, a common species easily adaptable to the country`s climatic conditions, was used in the removal of organic load from sewage discharge with an efficiency between 61% and 90%. Final effluent water quality after treatment was in compliance with current national legislation. The results obtained demonstrate the effectiveness of such biological system as an innovative wastewater treatment alternative in countries with tropical climate